IDENTIFIKASI KARAKTERISTIK DAN FORMASI KAMPUNG MELAYU DI KOTA PONTIANAK - Zairin Zain; Zsazsa Pradnyaparamita Candra Dewi (NALARs, 2024)
As an ethnic group that has lived for generations on the coast of the Kapuas River, West Kalimantan, many Malay villages have been formed and developed. Even though they are in the same city and tribe, each village has different characteristics as a form of adjustment to the conditions of the area where each community group lives. Characteristics can also be found in the formation or pattern of village settlements. Therefore, this paper aims to identify the factors and formations of Malay villages in Pontianak City, especially Tambelan Sampit Village, Bansir Village, and Beting Village. The qualitative descriptive research method with the comparative study approach used resulted in the discovery that the pattern of settlements in Kampung Melayu in Pontianak City follows the street circulation pattern, the direction of the buildings facing the Kapuas River and characteristics of each village is due to environmental influences or habits from another tribes. Sebagai etnis yang telah menetap turun-temurun di pesisir Sungai Kapuas, Kalimantan Barat, telah banyak kampung-kampung Melayu yang terbentuk dan berkembang. Walaupun berada di satu kota dan suku yang sama, tentunya setiap kampung memiliki perbedaan karakteristik sebagai bentuk penyesuaian kondisi daerah yang ditinggali masing-masing kelompok masyarakat. Karakteristik juga dapat ditemukan dari bentuk formasi atau pola permukiman kampung. Oleh karena itu, tulisan ini bertujuan untuk mengidentifikasi karakteristik dan formasi pada kampung-kampung Melayu di Kota Pontianak, khususnya Kampung Tambelan Sampit, Kampung Bansir, dan Kampung Beting. Metode penelitian deskriptif kualitatif dengan pendekatan studi komparasi yang digunakan menghasilkan penemuan bahwa pola permukiman pada Kampung Melayu di Kota Pontianak mengikuti pola sirkulasi jalan, arah bangunan tetap menghadap ke Sungai Kapuas dan karakteristik pada masing-masing kampung karena pengaruh lingkungan atau kebiasaan dari suku lain.